2014
DOI: 10.12659/msm.890126
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic analysis of modern dance movement “stag jump” within the context of impact loads, injury to the locomotor system and its prevention

Abstract: BackgroundThis paper presents a case study of kinematic analysis of the modern dance movement known as the “stag jump”. Detailed analysis of the kinematic structure of this movement as performed by the dancers, accompanied by measurements of impact forces during landing, will allow the authors to determine, in subsequent model-based research phases, the forces acting in knee joints of the lower landing limb.Material/MethodsTwo professional modern dancers participated in the study: a male and a female. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The last mentioned item was used in this investigation to divide the study subjects into groups. Interestingly, previous studies have shown that an intense training program begun at the age of 10 leads to specific structure and appearance of the dancer's musculoskeletal system [33][34][35][36]. First of all, due to repeated impact forces the increased bone mineralization is observed in the body parts which are regularly loaded [33,35,37].…”
Section: Plos Onementioning
confidence: 99%
“…The last mentioned item was used in this investigation to divide the study subjects into groups. Interestingly, previous studies have shown that an intense training program begun at the age of 10 leads to specific structure and appearance of the dancer's musculoskeletal system [33][34][35][36]. First of all, due to repeated impact forces the increased bone mineralization is observed in the body parts which are regularly loaded [33,35,37].…”
Section: Plos Onementioning
confidence: 99%
“…This also serves to search for correlations between the kinematic parameters of movement [36]. Many of these methods have also been used to assess the risk of injuries in professional sports [12,15,33].…”
Section: Characteristics Of Motor System Loading In Step Aerobicsmentioning
confidence: 99%
“…To reduce both injury incidence and prevalence, it is crucial to implement effective injury prevention strategies and rehabilitation, biomechanically safe and efficient technique training practices, and improved dance and gymnastics pedagogy. Research which has been carried out so far in dance biomechanics has focused on impact (e.g., jumps) and high pressure (e.g., pirouettes) movements as well as describing typical ballet movements [7,8]. The aim of this study was to compare kinetics parameters between two types of landing after performing front split leaps.…”
Section: Introductionmentioning
confidence: 99%